La representación de la figura humana en los manuscritos mayas coloniales de Chilam Balam - Florencia Scandar (Journal de la Société des Américanistes, 2023)
In this article I study the forms of representation of the human figure in the colonial Books of Chilam Balam. After a review of the canons of postclassic maya representation, I analyze some Chilam Balam images, pointing out the prehispanic characteristics that persist, and which can explain the apparently careless draughtsmanship of these representations. Finally, I  consider these images as the result of a complex process that led to a new visual tradition.